ANALISIS KASUS DELIK PIDANA MENGENAI PENCURIAN DENGAN PEMBERATAN : STUDI PUTUSAN NOMOR 125/PID.B/2018/PN.KIS - Syarofuddin, Muhammad (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
Indonesia is a constitutional state which refers to all regulations made by the state. Law is used to establish a set of rules to protect the interests of society in order to avoid prolonged social conflicts. This is in line with the highest source of law that upholds human rights contained in Article 1 paragraph (3) of the 1945 Constitution. In this context, strafrecht, which refers to all rules containing orders and prohibitions with penalties for violations, has an important role. One form of crime that often occurs in society is theft. Ordinary theft is a common type of theft, while other types of theft involve special circumstances or additional elements. Examples are aggravated theft, petty theft, violent theft, and family theft. In court decision no. 125/Pid.B/2018/PN.Kis, there is an analysis of cases of theft by weighting which is in the spotlight.